The Large GTPase Mx1 Is Involved in Apical Transport in MDCK Cells. (14th July 2014) - Hoff, Florian; Greb, Christoph; Hollmann, Christina; Hönig, Ellena; Jacob, Ralf
<x xml:space="preserve">Abstract</x> In epithelial cells apical proteins are transported by specific transport carriers to the correct membrane domain. The composition of these carriers is heterogeneous and comprises components such as motor proteins, annexins, lectins, Rab GTPases and cargo molecules. Here, we provide biochemical and fluorescence microscopic data to show that the dynamin‐related large GTPase Mx1 is a component of post‐Golgi vesicles carrying the neurotrophin receptor p75NTR. Moreover, siRNA‐mediated depletion of Mx1 significantly decreased the transport efficiency of apical proteins in MDCK cells. In conclusion, Mx1 plays a crucial role in the delivery of cargo molecules to the apical membrane of epithelial cells. <inline-graphic xlink:href="ark:/27927/pgh11r1h5bx" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />